Trzy głosy o książce Włodzimierza Boleckiego Modalności modernizmu - Wyka, Marta; Szumna, Małgorzata; Chmurski, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The text is a commentary on the book Modalności modernizmu (“Modalities of Modernism”) by Włodzimierz Bolecki which is regarded here as a pioneer synthesis. The authors bring attention to Bolecki’s model of thinking about Central and Eastern European modernism and ponder about the new perspectives that this model opens up. Special emphasis is put on the questions of methodology and training of a new generation of interpreters who should be equipped with the competences essential for conducting this type of research. Also, the attention is brought to cognitive benefits resulting from the perspective combining the description of the typical features of not only Polish modernism but also the Modernisms of the countries of Central and Eastern Europe, and especially, which is ever more evident in this context, not self-evident, unique character of Polish literature of the 19th and 20th centuries and the Polish turn towards modern culture in the studies of the recent decades. A broader presentation of a regional perspective which is suggested in the book by Bolecki, could help to explain the empty space on the map of parallel transformations in close, and yet individually different countries of the region, forcing us to revise our previous ways of thinking about literature and culture of modernism, as well as the languages of its description.